Tinjauan Literatur: Pengaruh Pemberian Madu untuk Anak Diare - Desak Putu Kristian Purnamiasih; Putriyanti, C. Ermayani (Jurnal Kesehatan, 2022)
Diarrhea is an endemic disease that has the potential to cause Extraordinary Events (Kejadian Luar Biasa/KLB) and is still a contributor to mortality in Indonesia, especially in toddlers. The common management of diarrhea is using oral rehydration therapy (ORS) to prevent dehydration. Moreover, honey could be useful also in handling diarrhea since it has anti-bacterial elements in it. The purpose of this study was to determine the effect of giving honey in children with diarrhea. The method used was literature review. There were 9 research articles obtained, and they revealed that there is an effect of giving honey to children who have diarrhea. This effect was proven by a greater decrease in the degree of dehydration in children who were given honey and standard therapy, the frequency of bowel movements in children who were given honey, as well as the stool consistency which was getting better. Healing time for children with diarrhea who were given honey and standard therapy was faster than children who only received standard therapy.